The Status of Married Women’s Nationality in the World - Ali Marzban (International Journal of Multicultural and Multireligious Understanding, 2016)
Within the eighteenth century a college known as "The Unity System of Lovers Nationality" mentioned the theory that women should find the nationality with their husbands after marriage. Additionally, the nationality of men should be enforced on women. However, in the 20th century, a movement identified as feminism surfaced which resulted in the forming of a school called known as "System of Nationality Independence". This college advocated the parting of marriage and nationality and assumed that women's nationality should not change following marriage. These legal schools experienced different manifestations in the positive laws and regulations of different countries and it is sometimes hard to classify them into an individual legal college. The legal systems of countries can be categorized into two communities: legal systems advocating the imposition of husbands' nationality on wives; legal systems opposing the imposition of husbands' nationality on wives. This paper tries to comprise different systems of relationship between marriage and nationality.